Ferroptosis in diabetic cardiomyopathy: from its mechanisms to therapeutic strategies - Tian, Meimei; Huang, Xinli; Li, Min; Lou, Pingping; Ma, Huijie; Jiang, Xinli; Zhou, Yaru; Liu, Yan (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy (DCM) is defined as cardiac structural and functional abnormalities in diabetes, and cardiomyocyte death is the terminal event of DCM. Ferroptosis is an iron-dependent oxidative cell death. Evidence has indicated that iron overload and ferroptosis play important role in the pathogenesis of DCM. Mitochondria, as important organelle in iron homeostasis and ROS production, play a crucial role in cardiomyocyte ferroptosis under diabetes. Studies have shown some anti-diabetic medicine, plant extracts and ferroptosis inhibitors, might improve DCM by alleviating ferroptosis. In this review, we systematically reviewed the evidences of ferroptosis in DCM. Antiferroptosis might be a promising therapeutic strategy for the treatment of DCM.